Diabetes mellitus in geriatric dogs from 7 to 10 years old - Vivanco-Luzuriaga, Freddy Fernando; Chalán-Flores, Paula (Revista Científica de la Facultad de Ciencias Veterinarias, 2022)
Diabetes Mellitus (DM) is a metabolic pathology that frequently occurs in dogs, especially in geriatric females. Its etiology lies in the inability of pancreatic β cells to produce insulin due to their destruction, which is called type 1 DM, which represents 50 % in dogs, or due to the development of insulin resistance, called type 2 DM, and clinical pictures associated with diestrus (heat stage) and pancreatitis. The presence of chronic hyperglycemia results in the appearance of classic clinical signs: polyuria, polydipsia, polyphagia and weight loss. This study was carried out to determine the presence of DM in dogs between the ages of 7 and 10 years old, through blood sampling, which was carried out during the months of August 2021 to January 2022. 60 dogs were sampled; the biochemical profile and values ​​reported by the glucometer were used; In this study, 41.67 % of geriatric patients tested positive for hyperglycemia, with a higher index in females; An early diagnosis, in addition to adequate treatment and monitoring, are key pieces for the control of the pathology.